A LANGUAGE FUNCTION: THE ANALYSIS OF CONATIVE FUNCTION IN MEGHAN MARKLE’S SPEECH - Fauzi Usrya Kanaza (Department of Master of Linguistic, Universitas Airlangga, 2020)
This paper examines the types of language functions used in the utterances and the one which is dominantly used in Meghan Markle’s speech. By applying qualitative method, the researcher analyze the utterance produced by Meghan Markle as the speaker, was delivering her speech. The researcher uses the five function of language proposed by Jakobson, they are referential function, conative function, emotive function, poetic function, and phatic function. The results show that there are five types of language functions used in Meghan Markle’s speech. The first most dominant function used is conative function (32%) which is found in 6 utterances. The second most dominant function is emotive function (26%) which is found in 5 utterances. Then referential function was found in 4 utterances (21%), phatic is found in 3 utterances (16%), while poetic function is found in 1 utterance only (5%). In addition, metalingual function is not used at all. Thus, it can be concluded that as the speaker, Meghan Markle wants to wants to influence her addressee through her utterances.Key word: Language, language function, speech